Motorcycle Accident Scenarios and Post-Crash Kinematics of Motorcyclists in Thailand - Carmai, J.; Koetniyom, S.; Sungduang, W.; Abu Kassim, K.A.; Ahmad, Y. (Journal of the Society of Automotive Engineers Malaysia, 2021)
This paper unveils a classification of motorcycle accident data in Thailand to identify common accident scenarios and impact parameters for multibody dynamics simulation of motorcycle crashes. The simulation results were analysed in terms of kinematics of riders and passengers as well as head impact locations. Motorcycle accident data revealed that rolling over without any contact with other vehicles was the most common scenario, while the side swipe was the most common type of crash involving other vehicles. The majority of accidents involved passenger cars with riders’ age ranging between 10-29 years. Serious and severe injuries accounted for 20% of the total number of casualties whereas minor abrasions and bruise accounted for 41%. Four common accident scenarios were identified together with a range of impact speeds, impact angles and impact points to generate impact conditions for multibody simulations. The simulation results revealed two patterns of global kinematics including (i) the rider together with the child pillion passenger were laterally projected towards the other vehicle as the other vehicle hit the lateral side of the motorcycle; and (ii) the rider together with the child pillion were launched forward in the direction of impact when the front wheel of the motorcycle hit the other vehicle. The vehicle hood was found to be the most frequently impacted area by the rider’s and child passenger’s head. The car windshield was the second most frequently impacted location for the rider’s head. For pick-up truck, the passenger window was the second most frequent area of impact. There was a moderate number of A-pillar contact on the car but such a situation was rare for the pick-up truck.